Mycobacterium salmoniphilum and M. chelonae in Captive Populations of Chinook Salmon. Issue 2 (29th March 2021) - Nguyen, Diem Thu; Marancik, David; Ware, Cynthia; Griffin, Matt J.; Soto, Esteban
Abstract: Chinook Salmon Oncorhynchus tshawytscha is a keystone fish species in the Pacific Northwest. In 2019, unusual mortalities occurred in two different populations of cultured fingerlings from the same facility in California, USA. The systems consist of outdoor, enclosed, flow‐through freshwater tanks that are maintained at 18 ± 1°C. Clinical signs and gross findings were only observed in one population and included abnormal swimming, inappetence, lethargy, skin discoloration, and the presence of multifocal nodular and ulcerative skin lesions. Microscopic lesions were infrequent and consisted of severe, locally extensive granulomatous dermatitis and myositis and mild, multifocal, granulomatous branchitis, myocarditis, and hepatitis. Intracellular acid‐fast organisms were observed within areas of granulomatous myositis. Posterior kidney swabs were collected and inoculated in nutrient‐rich and selective agar media and incubated at 25°C for 2 weeks. Visibly pure bacterial colonies were observed 7–10 d postinoculation. Partial sequences of 16S rRNA initially identified the recovered bacteria as members of the genus Mycobacterium . However, marked variability was observed among Mycobacterium spp. isolates by using repetitive extragenic palindromic polymerase chain reaction fingerprinting. Amplification and sequencing of the ribosomal RNA internal transcribed spacer, 65‐kDa heat shock protein, and RNA polymerase β‐subunit gene of the cultured isolates identified M. salmoniphilum and M. chelonae, discrete members of the M. chelonae‐abscessus complex, isolated from diseased Chinook Salmon fingerlings.